2015
DOI: 10.1158/1535-7163.mct-13-0951
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Blockade of EGFR and HER2 by New-Generation EGFR Tyrosine Kinase Inhibitor Enhances Radiation Effect in Bladder Cancer Cells

Abstract: Blockade of EGFR has been proved useful in enhancing the effect of radiotherapy, but the advantages of new-generation EGFR tyrosine kinase inhibitors (TKI) in radiosensitization are not well known. We used two human bladder cancer cells with wild-type EGFR to study the synergism between irradiation and afatinib (an EGFR/HER2 dual kinase inhibitor) or erlotinib (an EGFR kinase inhibitor). Here, we showed that afatinib has better radiosensitizing effect than erlotinib in increasing cancer cell killing, the perce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
0
20
0
2
Order By: Relevance
“…The epidermal growth factor receptor (EGFR) family has been implicated in tumor cell growth and differentiation, including EGFR, HER-2, HER-3, and HER-4 [ 6 ]. Many solid tumors have been found to overexpress EGFR, such as head and neck [ 7 ], lung [ 8 ], colon [ 9 ], breast [ 10 ], kidney [ 11 ], prostate, and bladder cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidermal growth factor receptor (EGFR) family has been implicated in tumor cell growth and differentiation, including EGFR, HER-2, HER-3, and HER-4 [ 6 ]. Many solid tumors have been found to overexpress EGFR, such as head and neck [ 7 ], lung [ 8 ], colon [ 9 ], breast [ 10 ], kidney [ 11 ], prostate, and bladder cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…HER-2 overexpression had studied extensively in breast carcinoma [ 14 ], and HER-2 is over-expressed in approximately 20% of primary invasive breast carcinomas [ 15 ] and is associated with poor prognosis [ 16 ]. Previous experiments have reported that EGFR and HER-2 are expressed in bladder cancer [ 17 ]. In the present study, we used immunohistochemistry to determine the expression of EGFR/HER-2, and to investigate their association with patients’ clinical features, pathological grade, and tumor recurrence, in hope of finding a new therapeutic strategy for bladder carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients receiving first‐generation EGFR‐tyrosine kinase inhibitor (TKI) undergo disease progression after 8.4 to 13.1 months of treatment, and the majority have local progression . It has been reported that EGFR‐TKI could increase radiosensitivity and that radiotherapy could reduce EGFR‐TKI resistance . Moreover, several studies showed effective local control by EGFR‐TKI combined with radiotherapy in metastatic sites of advanced non‐small cell lung cancer (NSCLC) harboring EGFR active mutations .…”
mentioning
confidence: 99%
“…Но едновременното блокиране на активираните от радиацията EGFR и HER2 сигнални пътища с тирозин-киназни инхибитори от ново поколение по-добре се отразява на потискането на растежа на раковите клетки на пикочния мехур както in vitro, така и in vivo. Това предполага, че приложението на ерлотиниб заедно с подходящ HER2-инхибитор ще доведе до по-добър терапевтичен ефект при лъчелечение на "привидно" нечувствителните ракови клетки на пикочния мехур (28).…”
Section: прицелна (таргетна) терапия при уроепителни заболяванияunclassified